A longitudinal assessment of privacy and territory establishment in a college residence hall setting - Benfield, Jacob A., author; Bell, Paul A., advisor (Colorado State University. Libraries, 2008)
College student retention/persistence is of great concern to higher education officials and has been linked to academic, social, and cultural factors that predict successful adjustment and satisfaction with the setting and the experience. The current research examines territory formation in a residence hall as one of the predictors of favorable outcomes for first-year students.

A sample of first-year Honors students (n = 110) assigned to a new residence hall participated in a five-wave longitudinal study to track changes in territoriality over their first 11 weeks on campus and to assess the impact of 17 territoriality indicators on student outcomes, including perceived stress and well-being. At each occasion, participants completed paper questionnaires related to assessment of their residence hall room and the student outcomes of interest. Personality traits such as privacy preference and dominance served as covariates. All participants had a roommate whom they had not met prior to assignment to the residence hall.

Unconditional growth models showed that 11 of the 17 territory components (e.g., perceived room carrying capacity, perception of the space as more private than public) demonstrated changes over time consistent with territory formation. The longitudinal data also showed that territory correlates (e.g., amount of personalization) were associated with positive student outcomes related to health, loneliness, happiness, life satisfaction, roommate satisfaction, and university satisfaction. Data from 2- or 3-week comparison samples (n = 66 and 28) and a separate analysis of the first 3 weeks of the 11-week sample showed very little change in territoriality and student outcomes, suggesting that residence hall territory establishment and the relationships associated with it require more than 3 weeks to develop.

The findings also imply the need to clarify between immediately occurring 'maintenance' behaviors and gradually developing 'attachment' cognitions. Previous research conducted with short personalization tasks or in public spaces suggested that individuals immediately form a territorial bond using social scripts. The current work suggests that stronger territorial cognitions likely take time to develop and are therefore only found in primary territories or after prolonged exposure, but once formed do predict positive outcomes, including overall satisfaction with a university.
Keywords: attachment; college; crowding; ownership; persistence; personalization; privacy; residence hall; social psychology; personality psychology; higher education